2019
DOI: 10.1016/j.clinthera.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Medication Nonadherence to Co-medication Compared to Immunosuppressants in Heart Transplant Recipients: Findings From the International Cross-sectional BRIGHT Study

Abstract: Purpose: To assess and compare the prevalence of medication nonadherence (MNA) (implementation and persistence) to immunosuppressants and co-medications in heart transplant recipients. Methods: MNA prevalence was assessed using the Basel Assessment of Adherence to Immunosuppressive Medications Scale (self-report) and compared using logistic regression in a 4-continent sample of 1397 heart transplant recipients from 36 heart transplant centers in 11 countries. Findings: MNA was significantly (a ¼ 0.05) higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The BAASIS is reliable, valid, short, simple to use, and sensitive to the taking and timing of immunosuppressive drugs 22 . It has been previously used to evaluate nonadherence to immunosuppressive medication among heart, liver, and lung transplant recipients 23–26 . Its score is reliable, as shown by its total Cronbach alpha coefficient of .697 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BAASIS is reliable, valid, short, simple to use, and sensitive to the taking and timing of immunosuppressive drugs 22 . It has been previously used to evaluate nonadherence to immunosuppressive medication among heart, liver, and lung transplant recipients 23–26 . Its score is reliable, as shown by its total Cronbach alpha coefficient of .697 26 …”
Section: Resultsmentioning
confidence: 99%
“…22 It has been previously used to evaluate nonadherence to immunosuppressive medication among heart, liver, and lung transplant recipients. [23][24][25][26] Its score is reliable, as shown by its total Cronbach alpha coefficient of .697. 26…”
Section: Basel Assessment Of Adherence To Immunosuppressive Medicatio...mentioning
confidence: 99%
“…Heart transplantation is the gold-standard treatment for refractory end-stage heart failure 1. Heart transplant recipients require numerous medications with complex treatment regimens, including immunosuppressants 2,3. Life-long immunosuppression is often critical for solid organ recipients to prevent graft rejection from an immune response 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Near-perfect adherence to immunosuppressants is crucial to achieving optimal long-term graft survival 2,6. However, many studies have revealed that immunosuppressant nonadherence (INA) has become a persistent problem among solid organ recipients 3,7…”
Section: Introductionmentioning
confidence: 99%
“…Cost-related medication nonadherence (CRMNA) consists of 3 behaviors, namely, not filling a prescription and skipping or reducing doses because of their cost, 9 and is a distinct concept from medication nonadherence as defined by the ABC taxonomy 10 (the prevalence and determinants of the latter have previously been reported as part of the BRIGHT study). 11 , 12 The 2014 Commonwealth Fund International Health Policy Survey of Older Adults assessed CRMNA, defined as either not filling a prescription or skipping doses within the last 12 months because of out-of-pocket (OOP) costs. 13 The lowest nonadherence rates occurred in France, Norway, Sweden, Switzerland, and the United Kingdom (<3%); the highest were observed in the United States (16.8%), Canada (8.3%), and Australia (6.8%).…”
mentioning
confidence: 99%